The effect of habitat changes along the urbanization gradient for breeding birds: an example from the Xiong’an New Area - Shilin Xie; Yuebo Su; Weihua Xu; Wenbo Cai; Xiaoke Wang; Fei Lu; Zhiyun Ouyang (PeerJ, 2019)
Background Because of its status as an ecocivilization pilot city, fundamental research on spatial distribution patterns and impact factors of the avian community within the Xiong’an New Area is necessary for future ecological planning and mitigation of negative impacts from future urbanization. Gradient research within small cities can provide important information for the development of urbanization gradient patterns of avian communities. Methods A total of 30 sample points within the urbanization gradient were selected, and avian communities and environmental variables were measured within a 50 m radius sample circle. Principal component regression analysis was used to analyze bird-environment relationships. The Sorensen dissimilarity index was used to calculate the beta-diversity. Results Our results showed that there was a significant urban-rural pattern with a gradient phenomenon in avian communities. Results of this study showed more resident, passenger and insectivore species, and a higher density of breeding insectivore and omnivore individuals appear in the urban fringe than in the other areas. A relatively high value of overall beta-diversity and spatial isolation probably exists among the three disjunct constructed regions. Both species richness and individual abundance were significantly influenced by the species diversity of the trees and foliage height diversity (FHD). Discussion Based on our results and our goal of avian species diversity conservation, we first suggest that urban green spaces be established and ensure a high complexity of vegetation structure as this is critically needed to increase avian species α-diversity within habitat patches. Second, different habitat types within and around the three constructed areas should be developed based on the important existing bird habitats to increase avian diversity in each city, especially in the areas within Xiongxian and Rongcheng that are well protected, and to elevate the beta-diversity of the total region. Finally, based on the biodiversity hotspots identified by this research, ecological corridors should be carefully planned to improve the stability of regional bird communities.